Sedation protocols in non-traumatic SAH (SPRINT-SAH): A cross-sectional survey among German-speaking neurointensivists - Schmidbauer, Moritz L.; Lanz, Hugo; Maskos, Andreas; Putz, Timon; Kunst, Stefan; Dimitriadis, Konstantinos (Frontiers in Neurology, 2023)
Background In subarachnoid hemorrhage (SAH), titrating sedation to find a balance between wakefulness with the ability to perform valid clinical examinations on the one hand, and deep sedation to minimize secondary brain damage on the other hand is challenging. However, data on this topic are scarce and current guidelines do not provide recommendations for sedation protocols in SAH. Methods We designed a web-based, cross-sectional survey for German-speaking neurointensivists to map the current standards regarding indication and monitoring of sedation, duration of prolonged sedation and biomarkers for the withdrawal of sedation. Results Overall, 17.4 % (37/213) of neurointensivists answered the questionnaire. Most of the participants were neurologists (54.1%, 20/37) and exhibited a long-standing experience in intensive care medicine (14.9 years, SD 8.3). Among indications for prolonged sedation in SAH, control of intracranial pressure (ICP) (94.6%) and status epilepticus (91.9%) were most significant. With regards to further complications in the course of the disease, therapy refractory ICP (45.9%, 17/37) and radiographic surrogates of elevated ICP such as parenchymal swelling (35.1%, 13/37) were most relevant to experts. Regular awakening trials were performed by 62.2% (23/37). All participants used clinical examination for the therapeutic monitoring of sedation depth. 83.8% (31/37) also used methods based on electroencephalography. As a mean duration of sedation before attempting an awakening trial in patients with unfavorable biomarkers neurointensivists suggested 4.5 days (SD 1.8) for good grade SAH, and 5.6 days (SD 2.8) for poor grade SAH, respectively. Many experts perform cranial imaging before definite withdrawal of sedation (84.6% (22/26)), and 63.6% (14/22) of the participants require absence of herniation, space-occupying lesions or global cerebral edema. ICP values tolerated for definite withdrawal were smaller compared to awakening trials (17.3 mmHg vs. 22.1mmHg) and patients were required to stay below the threshold for several hours (21.3 hours, SD 10.7). Conclusion Despite the paucity of clear recommendations for sedation management in SAH in the pre-existing literature, we found some level of agreement indicating clinical efficacy for certain clinical practices. By mapping the current standard, this survey may help to identify controversial aspects in clinical care of SAH and thereby streamline future research.